Charge/Discharge Asymmetry in Blended Lithium-Ion Electrodes. Issue 2 (1st January 2017) - Mao, Z.; Farkhondeh, M.; Pritzker, M.; Fowler, M.; Chen, Z.
Abstract : A multi-particle model for blended electrodes has been used to investigate the charge/discharge asymmetry in the response of a LiNi1/3 Mn1/3 Co1/3 O2 −LiMn2 O4 (NMC-LMO) blended cathode at various applied currents. The analysis suggests that the contribution of LMO to the end-capacity of the electrode increases as discharge at higher C-rates progresses but decreases during charge at the same rates. Dynamic analysis of the blended cathode shows that this asymmetric charge/discharge behavior of the blended electrode can be attributed to the difference in the equilibrium potentials of the two components depending on Li concentration and electrode composition and to the differences in the rate of solid-state diffusion of Li and kinetics limitations in LMO and NMC.